A Review of Insights and Research Progress on Hard Turning - S. Girisankar; S. Senthil Murugan; E. Shankar (Annals of "Dunarea de Jos" University of Galati, Fascicle XII, Welding Equipment and Technology, 2024)
Of late, due to the launch of improved machine tool designs and extremely hard cutting tools, “Hard Turning” (HT) or “Hard Finish Turning” (HFT) has turned out to be an innovative, cost-effective, and smart alternative to the traditional grinding and subsequent superfinishing processes. As a result, HT clenches the potential to produce excellent part quality in very little time along with negligible additional costs, which is considered to be a boon for the manufacturing industries. Hence, an attempt was made to review the development, key insights, and research progress in the HT process. So, a huge pool of HT studies has been reviewed to achieve a better understanding of the evolution and key insights namely process, workpiece materials, cutting inserts, machine tools, and machining parameters. Additionally, the effectiveness of HT using CBN (Cubic Boron Nitride) insert under different machining conditions is briefed. The review highlights the growing potential of HT in modern manufacturing and outlines the challenges and future research direction.